HADIS DHÂIF JIDDAN DALAM KITAB HADIS SAHIH AL-ALBANI (ANALISIS KRITIS ATAS KONSISTENSI AL-ALBANI DALAM KITAB SILSILAH AL-SAHIHAH) - Yaqin, Muhammad Ainul; Aminullah, Aminullah; Yusufa, Uun; Abbas, Rafid (FORUM PAEDAGOGIK, 2024)
This research aims to describe the hadith dha'if jiddan hadith dhâif jiddan in the Book of Hadith Sahih al-Albani (critical analysis of the consistency of al-Albani in the Book of Silsilah al-Sahihah). The research method uses qualitative research with descriptive analysis which is included in the library research category. Library research also utilizes library sources to obtain research data. The results of this research illustrate that in general, Muhammad Nasiruddin al-Albani's use of method of criticizing hadith does not have significant differences from the majority of muhaddisin. Because according to him he is a person who follows in the footsteps of previous scholars. The dhâif jiddan hadith in the book Silsilah al-Ahadis al-Sahihah became a serious polemic which caused al-Albani to be rejected by the muhaddis of his time. Al-Albani's attitude in applying his critical method is classified as inconsistent. Because there are several results of criticism of hadiths that violate it. Thus, the finding can be an important reference for muhaddis in tracing the track record of hadiths which is considered dha'if jiddan in the opinion of the ulama. Therefore, researchers in the same field are asked to be more critical in adhering to the rules for determining hadith based on the decisions of the ulama so that there are no inconsistencies in determining hadith in the future.